ANALISIS SPASIAL PENGARUH DANA PERIMBANGAN TERHADAP KETIMPANGAN PENDAPATAN DI PROVINSI JAWA TIMUR TAHUN 2008-2011 - Shofwatun Hasna (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2013)
The research objective was to analyze the influence and balance againts the imbalance of income in the province of east java in 2008-2011 by considering the spatial interconnection between the existing regencies/cities. The data Used on the research was panel data which approach was spatial econometric. The chosen model was then spatial error with fixed effect. The result shown that intercation performed between regencies/cities and its neighboring regencies/cities in east java was sufficiently high of which rate was 0,470 of range value 0 until 1. The performance of such interaction triggered the income imblance in east java. The spatial effect coming out can be abserved from value effect of each regencies/cities each of which was added by using intercept value on the model , The result indicatedthat spatial affected the increase of imbalance of income in all regencies/cities in east java except the regency of lamongan. By considering spatial aspect, it can be concluded that the increase of the balance of fund significantly gave positive impact to the income imbalance in east java. Other factors positively affecting were medical personel anf regional minimum wage (UMR), Nevertheless the factor of labors industry apparently negatively affected the index of imbalance in east java.